An Improved Discrete-Time Model for Heterogeneous High-Speed Train Traffic Flow - 许琰 贾斌 李明华 李新刚 (Communications in theoretical physics, 2016)
This paper aims to present a simulation model for heterogeneous high-speed train traffic flow based on an improved discrete-time model（IDTM）.In the proposed simulation model,four train control strategies,including departing strategy,traveling strategy,braking strategy,overtaking strategy,are well defined to optimize train movements.Based on the proposed simulation model,some characteristics of train traffic flow are investigated.Numerical results indicate that the departure time intervals,the station dwell time,the section length,and the ratio of fast trains have different influence on traffic capacity and train average velocity.The results can provide some theoretical support for the strategy making of railway departments.